Bacteriological Assessment of a Near-Dumpsite River in Obohia, Omoku, River State, Nigeria. - Onuotu, Aribibia-T Alex; Obomanu, Norah Henry; Dibia, Peace (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
Water samples were collected for bacteriological assessment of a river near a dumpsite in Obohia community, Omoku, Rivers State. The study was guided by four research objectives and corresponding research questions. To achieve these objectives, four freshwater samples were collected for bacteriological analysis from two sampling stations during both the wet and dry seasons. Results revealed the presence of coagulase-negative Staphylococcus, Staphylococcus aureus, Salmonella species, Escherichia coli, Klebsiella species, Proteus species, Shigella species, and Pseudomonas aeruginosa. Bacterial counts in the water samples exceeded the standard limits set by the World Health Organization (WHO) and the Environmental Protection Agency (EPA) for surface water. Seasonal variations were observed, with bacterial isolates totaling eleven during the wet season and eight during the dry season. It was recommended that appropriate water treatment measures be implemented, and regular pollution monitoring be conducted to prevent potential outbreaks of waterborne diseases in the community.